1984
DOI: 10.1055/s-2007-1023365
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Steal via a Large Anastomosis between the Coronary and Bronchial Arteries Successfully Treated by Surgical Division

Abstract: A 56-year-old woman is presented with a large coronary-artery-to-bronchial-artery anastomosis associated with aortitis syndrome. Her angina, which was the result of a coronary artery steal, was relieved by surgical division of the anastomotic vessel. Pulmonary artery obstruction, as a pulmonary lesion of aortitis syndrome, might increase the collateral flow from the coronary artery through the bronchial artery to the pulmonary circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…) supplying the apical segment of the right upper lobe. The anastomotic vessel of 3 mm diameter between the bronchial and coronary arteries already discussed was found in a patient with aortitis syndrome (Kawasuji et al, 1984). In this patient, in whom the segmental pulmonary artery to the right upper lobe was obstructed, all cardiac symptoms were relieved following surgical division of the anastomotic vessel.…”
Section: Pathologymentioning
confidence: 54%
See 2 more Smart Citations
“…) supplying the apical segment of the right upper lobe. The anastomotic vessel of 3 mm diameter between the bronchial and coronary arteries already discussed was found in a patient with aortitis syndrome (Kawasuji et al, 1984). In this patient, in whom the segmental pulmonary artery to the right upper lobe was obstructed, all cardiac symptoms were relieved following surgical division of the anastomotic vessel.…”
Section: Pathologymentioning
confidence: 54%
“…He also noted that, in pathologic conditions, the anastomotic arteries became tortuous and of larger caliber, albeit that the largest measured communications had diameters of no >1 mm (Moberg, 1967a, b). In this respect, Bjork (1966) reported the existence of communications with diameters of 2 mm, whereas Kawasuji et al (1984) measured an artery of 3 mm. Although conventional wisdom had suggested that the benefit of the anastomoses became evident only when both coronary arteries were obstructed, Sanerkin (1968) reported an instance in which extracardiac anastomoses of considerable caliber were formed in the setting of occlusion of a single coronary artery.…”
Section: Morphology Of the Anastomosesmentioning
confidence: 99%
See 1 more Smart Citation
“…Vessels can increase in caliber and become tortuous [ 10 ]. The diameters range from less than 1 mm up to 3 mm [ 25 - 30 ]. Vessels may reach a diameter of 2 mm in one out of eight patients [ 28 , 29 ]-Kawasuji reported a vessel that reached 3 mm in diameter [ 30 ].…”
Section: The Nature Of Nccmbfmentioning
confidence: 99%
“…In addition to our previous report [40], where we analyzed the coronary artery lesions documented in the literature from findings by angiography, surgery, and autopsy, there are many possible pathophysiological mechanisms in the development of coronary artery involvement: (1) coronary ostial stenosis secondary to proliferation of the aortic intima and contraction of the fibrotic media and adventitia that occur in the aorta, (2) stenosis due to extension of the aortic inflammation into the coronary artery, (3) stenosis at skip lesions due to inflammation of the coronary artery itself (eoronary arteritis), (4) coronary artery stenosis due to extrinsic constriction caused by periarteritis of the aorta or pulmonary artery, or associated pericarditis, (5) coronary artery thrombosis secondary to coronary arteritis [41], (6) coronary aneurysm with or without thrombus formation [41][42][43], (7) coronary steal syndrome due to coronary fistula communicating to the bronchial or pulmonary artery [44][45][46][47][48], and (8) compression of the coronary artery by aneurysm of the aortic sinus [49] (Fig. 4).…”
Section: Cardiac Involvementmentioning
confidence: 99%